A Letter from the Editor. Issue 1 (12th February 2019) - MILLER, DALE E.
Abstract : As editor in chief of Utilitas, it is my great pleasure to announce the appointment of two new associate editors. Dr. Emmanuelle de Champs is Professor of British History and Civilisation at the University of Cergy-Pontoise. She is the author of Enlightenment and Utility: Bentham in France, Bentham in French (Cambridge University Press, 2015) and La déontologie politique ou La pensée constitutionnelle de Jeremy Bentham (Droz, 2008). Dr. Holly Smith is Distinguished Professor of Philosophy at Rutgers University. Her Making Morality Work has just been published by Oxford University Press. So we have now strengthen our editorial roster in both the history of ideas and contemporary moral philosophy.